BIOLOGICAL POTENTIAL OF BENZOXAZOLE DERIVATIVES: AN UPDATED REVIEW - KAMAL, UDDIN; JAVED, NAIM MOHD; ARUN, KUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: Heterocycles exhibited an extensive role in the medicinal chemistry for the development of pharmaceutically active molecules. A heterocyclic scaffold is responsible for the therapeutic potential of majority of synthesized drug molecules. Therapeutic changes in the drug molecules related to the slight changes in the heterocyclic moiety. Benzoxazole and its derivatives showed potent and significant pharmacological activities. The main objective of our study is to impart updated information about synthesized benzoxazole derivatives and their biological potential against numerous diseases. Methods: A literature search was directed on the databases, namely, in MDPI, Science direct, PubMed, Springer, Taylor, and Francis by searching different keywords “Benzoxazole,” antimicrobial activity, anticancer activity, antitubercular, anti-inflammatory, analgesic, and anthelmintic activity. Conclusion: This review may radiate the path of researchers that are working to synthesized novel benzoxazole derivatives in the prospects of effectiveness and safety. Nonetheless, further in vivo and clinical studies are warranted on the potential derivatives of benzoxazole.